DIVERSIFIKASI PRODUK PENDEKATAN ISLAMIC ETHIC DALAM MENINGKATKAN OMSET BISNIS RETAIL - Taufik Aris Saputra; Aang Kunaifi; Siti Azizah (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2021)
This article aims to determine the motivating based on Islamic business ethics in anticipation of external changes, then obtaining empirical data regarding forms of product diversification that are relevant and effective in an effort to maintain and increase turnover in the retail business. In order to obtain accurate information and data, apart from reviewing the literature on Islamic law sources, related research articles, as well as information from primary sources from retail business actors. Thus, comprehensive data will be obtained to be analyzed as material to obtain accurate conclusions. Based on the data and the results of qualitative data analysis in this study, it was found that the motivation of Islamic business ethics is very strong to be the basis for making changes or in the form of diversification. Economically and managerial, concentric diversification is considered the most applicable to be done, although to measure the level of effectiveness it takes a relatively long time. Through the discussion and conclusions in this article, it is hoped that readers and retail business people in particular can find the right solution in facing intense competition and changes in external conditions such as pandemics and economic crises. For the next researcher, a quantitative test can be carried out regarding the influence of motivation and concentration diversification in increasing retail business turnover.